2020
DOI: 10.31635/ccschem.020.201900080
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polyselenoureas for Selective Gold Recovery Prepared from Catalyst-Free Multicomponent Polymerizations of Elemental Selenium

Abstract: Selenium-containing polymers with fascinating functionalities such as stimuli-responsive property, enzyme mimics, antioxidant activity, promotion of immune-cell activity, anticancer activity, and controlled delivery property, are highly desired, but rarely developed due to their underexplored synthetic methods. Herein, through careful design of monomeric structures and polymerization conditions, we report a series of catalyst-free multicomponent polymerizations (MCPs) of elemental selenium with aliphatic/aroma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…However, current routes to construct sulfur-rich polymers, especially well-defined ones still remain rare due to the limitations on the easily available sulfur-containing feedstocks. Elemental sulfur is a promising sulfur source, and its multicomponent copolymerization has been extensively studied to deliver polythioureas or polythioamides. While this strategy is facile and effective, the insolubility of the elemental sulfur usually leads to unsatisfied reactivity and broad polydispersity index ( Đ ) . Uncontrolled polymerization behavior also tortures other dithiols and thiolactones involved synthetic strategies. In contrast, ring-opening polymerization (ROP) and ring-opening copolymerization (ROCOP) are promising alternatives to target well-defined polymers in a controlled manner. A variety of sulfur-containing monomers have been demonstrated to be able to give well-defined polymers in mild conditions, as exemplified by poly­(thioester)­s through ROCOP of cyclic thioanhydrides and episulfides. ,, Besides, ROCOP of heteroallene comonomers (CS 2 , COS) with epoxides and episulfides offers an atom-economical approach to sulfur-containing macromolecules, however, tailor-made catalysts and monomer combinations are generally required to mitigate the involved oxygen–sulfur exchange side reactions. …”
mentioning
confidence: 99%
“…However, current routes to construct sulfur-rich polymers, especially well-defined ones still remain rare due to the limitations on the easily available sulfur-containing feedstocks. Elemental sulfur is a promising sulfur source, and its multicomponent copolymerization has been extensively studied to deliver polythioureas or polythioamides. While this strategy is facile and effective, the insolubility of the elemental sulfur usually leads to unsatisfied reactivity and broad polydispersity index ( Đ ) . Uncontrolled polymerization behavior also tortures other dithiols and thiolactones involved synthetic strategies. In contrast, ring-opening polymerization (ROP) and ring-opening copolymerization (ROCOP) are promising alternatives to target well-defined polymers in a controlled manner. A variety of sulfur-containing monomers have been demonstrated to be able to give well-defined polymers in mild conditions, as exemplified by poly­(thioester)­s through ROCOP of cyclic thioanhydrides and episulfides. ,, Besides, ROCOP of heteroallene comonomers (CS 2 , COS) with epoxides and episulfides offers an atom-economical approach to sulfur-containing macromolecules, however, tailor-made catalysts and monomer combinations are generally required to mitigate the involved oxygen–sulfur exchange side reactions. …”
mentioning
confidence: 99%
“…To meet the high annual demand for gold, a large part of gold is recycled from gold-containing industrial wastes such as waste circuit boards. , Conventional methods for gold extraction usually suffered from the toxicity of inorganic cyanide and hypochlorite, extreme pH conditions, limited efficiency, and environmental problems. In the recent few years, some green strategies have been developed for effective gold enrichment, such as based on the strong coordination of Au 3+ with sulfur or selenium in hydrophobic polymers, , or complexation with nitrogen atoms especially those involved in metal–organic framework materials, as well as the bacteria-enrichment method . Encouraged by the highly selective and sensitive detection of Au 3+ by P 1e / 2a / 3 , we envisioned that this nitrogen-rich polymer might also be useful for gold enrichment.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Wu et al reported the synthesis of functionalized and structurally diverse polyselenoureas via catalyst-free and solvent-free MC polymerizations of elemental Se, diisocyanides, and aliphatic/aromatic diamines. It is worth noting that the obtained polyselenoureas encompassed enhanced thermal stability and solubility, long-term stability, and the potential extraction of gold ions (Au 3+ ) from mixed-metal ion solutions ( Scheme 43 ) [ 91 ].…”
Section: The One-pot Multicomponent Combinatorial Synthesis Of Ose Co...mentioning
confidence: 99%